Inherited ADAMTS13 mutations associated with Thrombotic Thrombocytopenic Purpura: a short review and update. (1st January 2023) - Markham-Lee, Zoe; Morgan, Neil V.; Emsley, Jonas
Abstract: ADAMTS13 is a plasma metalloprotease with the primary function of cleaving VWF to maintain hemostasis. Circulating ADAMTS13 is in the closed conformation until blood vessel injury triggers a VWF-dependant activation to the open active form of the protein. ADAMTS13 is a multi-domain protein with the domains broadly functioning to interact and cleave VWF or maintain global latency of ADAMTS13. Thrombotic Thrombocytopenic Purpura is a disease characterized by excessive thrombi formation in the microvasculature, diagnosis is made when ADAMTS13 activity is <10%. In the hereditary form, a variety of mutations are found throughout all domains of ADAMTS13, examples are given alongside details of each domain in this article. ADAMTS13 mutations can inhibit the binding and cleavage of VWF directly or indirectly through reduced secretion, leading to increased size of VWF multimers and platelet recruitment. Molecular characterization of ADAMTS13 may provide insight into the mechanisms of TTP to aid in both scientific and clinical research.